1995
DOI: 10.1002/pi.1995.210370206
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization of some silicon‐ and tin‐containing monomers

Abstract: Plasma polymerization of several selected saturated and unsaturated silicon‐ and tin‐containing monomers, such as vinyltriethoxysilane (VTES), 3‐aminopropyltriethoxysilane (APTS), hexamethyldisiloxane (HMDS), hexabutyldistannoxane (HBDS) and tetraethylstannane (TES), were examined in terms of the following selected plasma operational parameters: discharge time (t), flow rate of monomer (F) and power input (W). For the initial deposition rates (DR), the following empirical equation was proposed: DR = k ta Fb Wc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…FTIR spectra shown in Figure 1 were for c‐silica (a) and m ‐silica (b). The feature at 914 cm −1 in trace b was assigned to epoxy groups; those at 2857 and 2926 cm −1 were because of CH stretching 24–28. This indicated that SSO based on GPMS was chemically bonded to silica.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…FTIR spectra shown in Figure 1 were for c‐silica (a) and m ‐silica (b). The feature at 914 cm −1 in trace b was assigned to epoxy groups; those at 2857 and 2926 cm −1 were because of CH stretching 24–28. This indicated that SSO based on GPMS was chemically bonded to silica.…”
Section: Resultsmentioning
confidence: 95%
“…For the spectrum of IPN, i.e., the system after curing, the bands at 1855, 1777, and 921 cm −1 disappeared and the bands at 3700–3320 cm −1 (OH) and 1738 cm −1 (COO) enhanced, indicating the reaction between DGEBA and the hardener. In addition, the bands at 2160 and 1414 cm −1 disappeared, which indicated the hydrosilylation between PDMS 6, 24–29…”
Section: Resultsmentioning
confidence: 99%
“…Silane‐based coupling agents, most frequently γ‐aminopropyltriethoxysilane (APTS), were used to improve the surface adhesion in various polymer composites,6 to modify the surface of polypropylene7 and polyethylene films,8 and for the preparation of silica hybrid materials by in situ solvent (THF) gel process using a maleic anhydride (12 wt %) styrene random copolymer/tetraethoxysilane/APTS system 9. The interactions of MA–styrene or MA–α‐olefins alternating copolymers with APTS were studied by means of FTIR–ART spectroscopy 10.…”
Section: Introductionmentioning
confidence: 99%